Investigating the Relationship Between Postpartum Depression, Antenatal Depression, Corona Disease Anxiety, and Personality Traits During the COVID-19 Pandemic - Nejad, Hanieh Soltani; Mohtasham, Fatemeh; Ramezanzadeh, Mahjoubeh; Arashlouei, Azam Zare; Ahmadi, Atefeh; Dadvar, Adele; Iranmanesh, Saleheh; Mirmahmoodi, Motahare (Coronaviruses, 2026)
Introduction and AimPostpartum depression has a profound impact, both physically and psychologically, on both the mother and her newborn. With a focus on the prevalent psychological complications following the onset of this condition, this study aimed to explore the correlation between antenatal depression and corona disease anxiety, personality traits, and postpartum depression during the COVID-19 pandemic.Materials and MethodsThis cross-sectional descriptive-analytical study investigated women receiving care at health centers affiliated with Kerman University of Medical Sciences during the last month of their pregnancy and the postpartum period in 2022. Following the acquisition of informed consent, participants were assessed using various measures, including demographic and obstetric information, the Edinburgh Postnatal Depression Scale, the Corona Disease Anxiety Scale (CDAS), and the NEO Personality Inventory-Revised during their third trimester of pregnancy. The same group of participants completed the Edinburgh Depression Scale and the Corona Disease Anxiety Scale (CDAS) 4-6 weeks after childbirth.Results and DiscussionThere was a significant correlation between family income, unwanted pregnancy as perceived by both the mother and father, and antenatal depression. Additionally, marital satisfaction played a significant role in postpartum depression. Furthermore, antenatal depression was significantly associated with neuroticism, agreeableness, and physical symptoms related to corona disease anxiety. Personality traits, with the exception of extroversion and conscientiousness, and various domains of corona disease anxiety, excluding psychological symptoms, were also significantly associated with postpartum depression.ConclusionDuring pandemics or epidemics, such as the COVID-19 outbreak, experiencing mental distress during pregnancy can contribute to mental health issues during the postpartum period. This risk is particularly true in individuals with unique personality traits, emphasizing the need for increased focus on mental health within prenatal care during these crises.
Keywords: personality traits